Application of the weighted product (WP) method in determining construction project priorities at PT. Graha Karya Perkasa Medan - Siti Azzahra (Jurnal Sains, Teknologi & Komputer, 2026)
PT. Graha Karya Perkasa is a company engaged in the construction and infrastructure sector, so it requires an appropriate decision-making process in determining which projects should be prioritized. This study aims to determine the priority order of three projects, namely the construction of the MBG Warehouse, the construction of the Flyover Bridge, and the construction of the Dam using the Weighted Product (WP) method. The assessment is carried out based on three main criteria, namely cost, duration, and quality. Research data was obtained through interviews with project heads and available planning documents. Based on the results of calculations using the Weighted Product method, the Flyover Bridge project is the project with the highest priority value, followed by the MBG Warehouse and the Dam. The Weighted Product method has been proven to be able to provide objective results in the process of determining project priorities.